Diasporic generations: Memory, politics, and nation among Cubans in Spain - Berg, M (Berghahn Books, 2011)
Interpretations of the background to the Cuban diaspora – a political revolution and the subsequent radical transformation of the society and economy towards socialism – are politicised and highly contested. The Miami-based Cuban diaspora has had extraordinary success in putting its case high on the US political agenda and in capturing world media attention, but in the process the multiplicity of experiences within the diaspora has been overshadowed. This book gives voice to diasporic Cubans living in Spain, the former colonial ruler of Cuba. By focusing on their lived experiences of displacement, the book brings to light imaginative, narrative re-creations of the nation from afar. Drawing on extensive ethnographic fieldwork, the book argues that the Cuban diaspora in Spain consists of three diasporic generations, generated through distinct migratory experiences. This constitutes an important step forward in understanding the dynamics of memory-making and social differentiation within diasporas, and in appreciating why people within the same diaspora engage in different modes of transnational practices and homeland relations.